2000
DOI: 10.1359/jbmr.2000.15.6.1169
|View full text |Cite
|
Sign up to set email alerts
|

Maturation State Determines the Response of Osteogenic Cells to Surface Roughness and 1,25-Dihydroxyvitamin D3

Abstract: In this study we assessed whether osteogenic cells respond in a differential manner to changes in surface roughness depending on their maturation state. Previous studies using MG63 osteoblast-like cells, hypothesized to be at a relatively immature maturation state, showed that proliferation was inhibited and differentiation (osteocalcin production) was stimulated by culture on titanium (Ti) surfaces of increasing roughness. At harvest, cell number, alkaline phosphatase-specific activity, and production of oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 34 publications
6
100
2
Order By: Relevance
“…This study supports other observations in our lab showing that alkaline phosphatase is regulated separately from osteocalcin [24]. Alkaline phosphatase activity is increased in osteoblast cultures prior to the onset of calcification, whereas osteocalcin synthesis occurs as calcification is initiated [18,23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study supports other observations in our lab showing that alkaline phosphatase is regulated separately from osteocalcin [24]. Alkaline phosphatase activity is increased in osteoblast cultures prior to the onset of calcification, whereas osteocalcin synthesis occurs as calcification is initiated [18,23].…”
Section: Discussionsupporting
confidence: 92%
“…When MG63 human osteoblastlike osteosarcoma cells [5], fetal rat calvarial cells [24], or normal human osteoblast cells (NHOst) [25] are cultured on titanium disks with varying microtopographies, there is a roughness-dependent effect on phenotypic expression. As roughness increases, proliferation decreases.…”
Section: Introductionmentioning
confidence: 99%
“…They are a well characterized osteoblastlike cell culture model for assessing responses to Ti surface microstructure (24, 51) and surface energy (28). Observations using MG63 cells have been confirmed by using normal human osteoblasts (52), normal mouse calvarial osteoblasts, fetal rat calvarial cells, and other osteoblast cell lines (53), and the results correlate with clinical performance in animals and humans (3-5, 7, 8).…”
Section: Resultsmentioning
confidence: 92%
“…Nonetheless, Lohmann et al 35) showed -using three types of osteogenic cell lines -that osteoblastic cells responded in a differential manner to changes in surface roughness depending on their maturation state. In other words, the types and conditions of cells in the osteoblast lineage may affect proliferation responses to surface roughness.…”
Section: Discussionmentioning
confidence: 99%